Innovative percutaneous antegrade clearance of intrahepatic and extrahepatic biliary stones with the use of a hysterosalpingography catheter. Issue 4 (April 2015) - Patrone, Lorenzo; Parthipun, Aneeta; Diamantopoulos, Athanasios; Pinna, Francesco; Valdata, Alessandro; Ahmed, Irfan; Filauro, Marco; Sabharwal, Tarun; de Caro, Giovanni
<x xml:space="preserve">Abstract</x> Objectives We present a novel modified technique of percutaneous antegrade clearance of intrahepatic and common bile duct stones with the use of a hysterosalpingography balloon (HSG) catheter. Methods Technical tips and techniques used, along with the clinical results obtained in six patients whom we treated over a 6-month period have been described. Results The HSG balloon catheter is shown to demonstrate superior pushability, flexibility, and maneuverability in comparison with other previously described compliant balloons. Conclusions The HSG balloon catheter is shown to be a really good device to remove intrahepatic and common bile duct stones percutaneously, allowing, where required, access to both the right and the left intrahepatic biliary systems from a single and smaller Fr hepatic bile duct access.